Critiquing South Africa’s General Intelligence Laws Amendment Bill: Drawing Lessons from Germany’s Comprehensive Surveillance Oversight - Casper Lӧtter (Obiter, 2024)
Governments have a responsibility to manage intelligence surveillance oversight without overreach as a fundamental principle of democracy. This delicate equilibrium can only be achieved through collaboration with civil society and a strong allegiance to the rule of law. The article delves into and underscores the chasm that has opened between a weak oversight function and an unchecked, inadequately regulated overreach in South African intelligence surveillance, a remnant of the Zuma era. It commences with an overview of South Africa’s General Intelligence Laws Amendment Bill 40 of 2023 and goes on to provide a synopsis of Germany’s oversight function. A comparative analysis of the German intelligence oversight model is undertaken, examining its strengths and vulnerabilities. Principled, measured and calibrated recommendations are proposed, based on best practices related to the German oversight model.